Recovering the Irrecoverable: Blackness, Melancholy, and Duplicities That Bind - Winters, Joseph (Religions, 2021)
In this article, I critically engage Stephen Best’s provocative text, None Like Us. The article agrees with Best’s general concerns regarding longings for a unified black community or a We before the collective crime of slavery. Yet I contend that melancholy, which Best associates with black studies’ desire to recover a lost object, can be read in a different direction, one that includes both attachment and wound, investment and dissolution. To think with and against Best, I examine Spike Lee’s School Daze in conversation with Freud, Benjamin, and Morrison.